Re-Designing the role of Phalak and Phalam in Modern Lao Ramayana - Gisa Jähnichen, (Wacana Seni Journal of Arts Discourse, 2009)
Parts of the story of Phalak and Phalam (Lakshman and Rama of the classical Ramayana) are the inspiration of dance traditions in past and present Laos. In the past 25 years, special local styles and the varying understanding of different roles have been replaced by a uniformed frame of dance performances. Nevertheless, dancers and musicians from families with a long tradition in dancing and teaching classical dance and its music have been ?ghting against the displacement of local styles.In Vientiane, the capital of Laos, special complementary aesthetics were re-designed at the National Academy for Dance and Music. The main male roles Phalak and Phalam emerge in a female interpretation. They are not only performed by female dancers, but they are associated with contemporary female appearances. The understanding of these roles requires a gender opposing performance, where female dancers seem to be the most appropriate due to special physical and emotional demands of the dance drama. In Vientiane, female dancers in these two important traditional roles became a vital part of modern cultural self-understanding that underlines differences with other local cultures in Laos.The revitalisation of dance traditions in Vientiane was to a great extent supported by the “Archives of Traditional Music in Laos” at the National Library in Vientiane. Re-researching historical sources, which help to understand local adaptations of seemingly well known literature, and creating audiovisual teaching materials were further outcomes of joint efforts, which were undertaken since 1999.